Synthesis, biological properties and effects of trans-2-(substituted amino)-cyclohehyl esters. - Vu Hon Shon; D. M. Zverev; N. Yu. Borisova; E. Yu. Afanasieva; T. P. Kolobova; E. Ya. Borisova (Тонкие химические технологии, 2007)
A series of trans-2-(substituted amino)-cyclohehyl esters have been synthesized and examined for pharmacological activity. Significant responses have been noted with these compounds as ant arrhythmic substances.